HYDROGEOCHEMICAL DESCRIPTION OF GROUNDWATER IN A COASTAL LOWLAND PLAIN NEAR THE ARIAKE SEA OF JAPAN - N. Cao Don; Mohan S. Kumar; H. Araki; H. Yamanishi (International Association of Lowland Technology, 2008)
In the management of water resources, quality of water is just as important as its quantity. In this paper, an investigation was undertaken to better understand the hydrogeochemistry and hydrologic framework of the Shiroishi plain in Saga, Kyushu, Japan. A network of production boreholes and wells distributed over the studied region were sampled and the waters were analyzed for major ions. The results reveal that, in areas near the shore, salinization is more serious at deeper layers. Geochemical analyses showed that the Shiroishi aquifer has bicarbonate sodium water, with an increase of electrical conductivity, sodium and bicarbonates contents.